2003
DOI: 10.1182/blood-2002-07-2085
|View full text |Cite
|
Sign up to set email alerts
|

In vitro identification of human pro-B cells that give rise to macrophages, natural killer cells, and T cells

Abstract: IntroductionEarly stages of human B-cell development can be identified by the expression of cytoplasmic and cell-surface markers and the ordered rearrangements of the V, D, and J gene segments that encode the variable domain of the immunoglobulin heavy-chain (IgH) locus. 1 Thus, D3J H rearrangements in pro-B cells precede the V3DJ H rearrangement in pre-B cells. The earliest B-cell precursors that carry a complete VDJ H rearrangement have been identified by their intracellular expression of a chain without lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 56 publications
6
33
2
Order By: Relevance
“…Strikingly, IgH rearrangements and CD127 expression were mutually exclusive, particularly within the gd/IM lineage, when Ig rearrangements were seen in 11/17 (65%) CD127 negative compared to only 2/15 (13%) CD127 positive cases; P ¼ 0.003. This is in keeping with IL7-mediated orientation towards a T/NK/dendritic-macrophage precursor, as recently described, 15 rather than towards the B-cell lineage. Among gd/IM T-ALLs, only 2/14 cCD79a þ /IgH D-J þ cases were CD127 þ compared to seven of the 11 cCD79aÀ/IgH D-J-cases (P ¼ 0.02).…”
Section: Il7ra/cd127 Expression Define Two Subgroups Of T-allssupporting
confidence: 89%
See 1 more Smart Citation
“…Strikingly, IgH rearrangements and CD127 expression were mutually exclusive, particularly within the gd/IM lineage, when Ig rearrangements were seen in 11/17 (65%) CD127 negative compared to only 2/15 (13%) CD127 positive cases; P ¼ 0.003. This is in keeping with IL7-mediated orientation towards a T/NK/dendritic-macrophage precursor, as recently described, 15 rather than towards the B-cell lineage. Among gd/IM T-ALLs, only 2/14 cCD79a þ /IgH D-J þ cases were CD127 þ compared to seven of the 11 cCD79aÀ/IgH D-J-cases (P ¼ 0.02).…”
Section: Il7ra/cd127 Expression Define Two Subgroups Of T-allssupporting
confidence: 89%
“…1,14 An early CD34 þ , CD19À, CD10À, cCD79a þ , CD127 þ cord blood B progenitor has recently been shown to demonstrate IgH DJ rearrangement and macrophage, natural killer (NK), B and T lymphoid potential. 15 IgH DJ rearrangements have also been reported in normal immature murine, 16 but not human, 12 thymocytes and in 22% of pediatric T-ALLs, particularly in TCRgd þ cases. 17 We have recently described a TCR-based classification which allows separation of T-ALLs into ab-lineage (TCRab/cTCRb expressing and/or TCRb VDJ rearranged T-ALLs) and gd lineage/immature (gd/IM) leukemias (TCRgd expressing or absence of complete TCRb rearrangement).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report stated that human B-cell progenitors obtained from cultures of cord blood CD34 ϩ CD10 Ϫ CD19 Ϫ cells gave rise to macrophages, NK cells, and T cells when exposed to the appropriate culture conditions. 23 Our study shows the lineage switch of human primary postnatal cells and further extends the existence of lineage switch to postmitotic cells. This notion is also supported by our observations in the microarray analysis that gene expression profiles of the resultant cells differed from those of the starting CD15 ϩ CD14 Ϫ neutrophils and were similar to those of CD14 ϩ cell-derived macrophages.…”
Section: Discussionsupporting
confidence: 73%
“…22 Thus, normal murine lymphoid progenitors may retain the potential to differentiate into macrophages. Reynaud et al 23 reported that human cord blood-derived pro-B cells with DJ H rearrangements of the immunoglobulin (Ig) locus generate macrophages, NK cells, and T cells. However, it is unknown whether the lineage switch occurs in normal human mature hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that human pro-B cells can give rise to macrophages in vitro. 6 Rare cases of H/DC neoplasms have been reported in patients with mature B-cell neoplasms. Vasef et al reported 3 patients with dendritic cell tumors associated with low-grade B-cell malignancies, 7 including a 59-year-old woman who developed a dendritic cell sarcoma 9 years following a diagnosis of follicular lymphoma (FL), grade 1.…”
Section: Introductionmentioning
confidence: 99%